Differences in functional traits of herbaceous plants in Sanjiang plain wetland under human disturbance gradient and their response strategies to environmental changes - Meng, Qiuyu; Liu, Zihe; Guo, Naixu; Liu, Jiping (Frontiers in Plant Science, 2026)
Using the Honghe Nature Reserve in the Sanjiang Plain as a case study, this research tests the central hypothesis that increasing anthropogenic disturbance intensity shifts the ecological strategies of dominant plant species along a resource-conservative to acquisitive spectrum, thereby progressively enhancing the role of soil properties as proximate drivers of trait variation. This hypothesized process unfolds sequentially: under low-intensity disturbance, direct physical stress acts as the primary filter on traits; at moderate intensity, disturbance begins altering soil conditions, shifting plant adaptation toward soil resource competition and increasing the explanatory power of soil factors; under high-intensity disturbance, profoundly transformed soil environments become the dominant proximate filter, selecting strongly for resource-acquisitive traits. We examined this framework by measuring leaf and root traits of 14 dominant herbaceous species and soil factors across 24 disturbance-gradient plots. Findings confirm distinct adaptive strategies: phosphorus-limited growth in light disturbance, conservative resource use in moderate disturbance, and a shift toward fast-return strategies in fertile, heavily disturbed soils. This study mechanistically traces the cascade from ultimate (anthropogenic disturbance) to proximate (soil) drivers of plant adaptation, providing a scientific basis for targeted wetland restoration that addresses disturbance legacies.